2005
DOI: 10.1111/j.1365-2966.2005.09397.x
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of the TW Hydrae association and the encounter with Vega

Abstract: We investigate the paths of several probable members of the young association around the star TW Hydrae (TWA) with accurate distances, proper motions and radial velocities. We find that three of the previously identified members, TWA 1, TWA 4 and TWA 11, together with two other young nearby stars, HD 139084 and HD 220476, form a rapidly expanding association with an expansion age of 4.7 ± 0.6 Myr. Initial velocities of member stars with respect to the common centre of mass range from 4 to 10 km s−1. A characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…4.1 and is identical to the value of σ v = 0.8 +0.3 −0.2 km s −1 derived by Mamajek (2005) in his analysis 2 . Makarov et al (2005) and de la Reza et al (2006) pioneered the idea of accurately deriving the dynamical age of the TWA. Makarov et al (2005) investigated the path of several proba-ble members of the association and showed that five objects form a rapidly expanding association with an expansion age of 4.7±0.6 My.…”
Section: Membership Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…4.1 and is identical to the value of σ v = 0.8 +0.3 −0.2 km s −1 derived by Mamajek (2005) in his analysis 2 . Makarov et al (2005) and de la Reza et al (2006) pioneered the idea of accurately deriving the dynamical age of the TWA. Makarov et al (2005) investigated the path of several proba-ble members of the association and showed that five objects form a rapidly expanding association with an expansion age of 4.7±0.6 My.…”
Section: Membership Analysismentioning
confidence: 99%
“…Makarov et al (2005) and de la Reza et al (2006) pioneered the idea of accurately deriving the dynamical age of the TWA. Makarov et al (2005) investigated the path of several proba-ble members of the association and showed that five objects form a rapidly expanding association with an expansion age of 4.7±0.6 My. De la Reza et al (2006) showed that four H stars belonging to the association were converging back in time toward a minimum volume corresponding to the dynamical age of the association.…”
Section: Membership Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…However, the likely complex dynamical evolution of TWA has led to several plausible evolutionary scenarios. Makarov et al (2005) attribute this complex evolution to a chance encounter with Vega, while Lawson & Crause (2005) suggest that TWA is composed of two separate groups, based on bimodal rotation period distributions with distinctly separate ages of $10 and $17 Myr. More recently, Barrado y Navascués (2006) found a conservative age of 10 þ10 À7 Myr by comparing ages from HR diagram isochrone comparisons (from BCAH98) and lithium abundances.…”
Section: Introductionmentioning
confidence: 99%